Molecular docking studies of selected medicinal drugs as dengue virus-2 protease inhibitors - Rufaidah Othman,; Rozana Othman,; Aida Baharuddin,; Nagasundara Ramanan Ramakrishnan,; Noorsaadah Abd Rahman,; Rohana Yusof,; Saiful Anuar Karsani, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Dengue is a potentially deadly disease with no effective drug. An in silico molecular docking was performed using Autodock 4.2.6 to investigate the molecular interactions between protease inhibitors, comprising antibiotic derivatives namely doxycycline (3), rolitetracycline (5) and a non-steroidal anti-inflammatory drug (NSAID), meclofenamic acid (4), against the NS2B-NS3 protease from dengue virus-2 (DENV-2). The non-competitive inhibitor (3) showed lower binding energy (-5.15 kcal/mol) than the predicted competitive inhibitors 4 and 5 (-3.64 and -3.21 kcal/mol, respectively). Structural analyses showed compound 3 that bound to a specific allosteric site, interacted with Lys74, a significant amino acid residue bonded to one of the catalytic triad, Asp75. Compounds 4 and 5 showed direct binding with two of the catalytic triad, His51 and Ser135, hence, predicted to be competitive inhibitors.